Analisis Keakuratan Arah Kiblat Masjid di Kecamatan Tanete Riattang Barat Kabupaten Bone - Andi Jusran (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2019)
This article examines and tests the accuracy of the direction of several mosques in Tanete Riattang Barat by using several methods, namely the Qibla azimuth method, Google Earth satellite imagery and using istiwa sticks. In this study, the author describe several mosques as samples and test the accuracy level of Qibla direction, where some people consider the issue of Qibla direction to be a classic problem. But in fact, this problem is still discussed and sometimes controversial. There are parties who agreed, some refused. It is important to note that the Qibla direction is the closest direction to the Ka'bah (Masjid al-Haram) through the great circle of the Earth, the direction where people want to pray so that the direction cannot be considered trivial or even insignificant, which can potentially cause conflict in community. For this reason, the determination of Qibla direction must be correct so that the perfection of worship can be achieved, thus minimizing the potential for conflict of understanding. Keywords : Qibla Direction; Azimuth Qibla; Google Earth; Istiwa Stick.